Review on Nasal Drug Delivery System and Their Application - Tariyal, Kanchan (Journal for Research in Applied Sciences and Biotechnology, 2024)
Nasal drug delivery has received a great deal of attention as a convenient, reliable, and promising method for the systemic administration of drugs. It is especially for those molecules which are ineffective orally and only effective if administered by injection. The nasal route of drug delivery has advantages over the other alternative systems of non-invasive drug administration. The present review is an attempt to provide some information concerning nasal drug delivery system such as limitations, advantages, mechanism of drug absorption, anatomy of nasal cavity, factors affecting of nasal drug delivery, strategies to enhance nasal absorption, strategies to extend duration of drug formulations within the nasal cavity, leading to improved nasal drug absorption, novel drug formulations, sorts of nasal drug delivery system with uses of nasal drug delivery in various diseases, and recent advancement of nasal delivery systems.